Vitamin D supplementation and outcomes in coronavirus disease 2019 (COVID-19) patients from the outbreak area of Lombardy, Italy - Cereda, Emanuele (Nutrition, 2021)
• Vitamin D has antiinflammatory and immunoregulatory functions. • The involvement of vitamin D in the pathophysiology of coronavirus disease 2019 (COVID-19) is still not clear. • Some studies support a link between vitamin D deficiency and worse COVID-19 outcomes. • Vitamin D may also enhance macrophage activation and aberrant immune response. • In our study, vitamin D supplementation was associated with a trend toward higher mortality. • Supplementation trials are crucial to clarify the role of vitamin D in COVID-19.